The Government Policy on Online-Based Transportation in the Era of Disruption - Nico Djundharto Djajasinga (Universitas Sultan Ageng Tirtayasa, 2022)
The purpose of this study is to analyze the challenges and constraints of government policy on online-based land transportation in the era of disruption. This research uses qualitative research design. The type of data used in this research is seconddary data. Sufficient data is needed as material for analysis in the discussion of this article. The data collection method used in this research is a literature study. Based on the analysis results, it can be concluded that the implementation of online transportation system policies in Indonesia has been able to improve the social welfare of some Indonesian people. However, there are still some obstacles in the social sphere in its implementation, such as government organizational structure, umbrella act, facilities, human resources, and the process. Meanwhile, blocks were also found from the driver's side, such as mobility gaps, differences in inaccessibility, the potential for accidents, and congestion, which can be a waste of energy.